Development of Simple Sequence Repeat Markers from Bacterial Artificial Chromosomes without Subcloning - X. Qi; S. Lindup; T.S. Pittaway; S. Allouis; M.D. Gale; K.M. Devos (BioTechniques)
Simple sequence repeats (SSRs) were isolated from pearl millet bacterial artificial clones (BACs) without any subcloning steps. SSR sequences were targeted using 3′ end anchored SSR primers. Flanking sequences were isolated by suppression PCR. In this pilot study, 25 SSR markers have been developed from 40 BAC pools, comprising a total of 384 clones. This novel way to develop new markers has the added advantage that mapping the SSR markers will anchor individual BACs to the genetic maps and, thus, facilitate the construction of BAC contigs.